Cover Picture: The Role of Microfabrication and Nanotechnology in the Development of Microbial Fuel Cells (Energy Technol. 10/2015). Issue 10 (7th October 2015) - Rojas, Jhonathan Prieto; Hussain, Muhammad M.
<x xml:space="preserve">Abstract</x> Microbial fuel cells (MFCs) make up an exciting and growing technology that promise to generate electricity using the bioelectrochemical processes of bacteria present in wastewater; this potential can be further expanded and developed by the use of mature microfabrication techniques and novel nanomaterials. In this Review, Jhonathan Prieto Rojas and Muhammad M. Hussain from King Abdullah University of Science and Technology, summarize the significant efforts to apply microfabrication techniques and integrate nanomaterials to build more efficient microsized MFCs, and provide some insights on both their advantages and challenges. Furthermore some important key considerations for scaling‐up and commercialization are also discussed, as well as some applications in real scenarios. More details can be found in the Review by Jhonathan Prieto Rojas et al. (DOI: 10.1002/ente.201500126).